Synthesis of diamido-bridged bis-pillar[5]arenes and tris-pillar[5]arenes for construction of unique [1]rotaxanes and bis-[1]rotaxanes - Han, Ying; Xu, Li-Ming; Nie, Cui-Yun; Jiang, Shuo; Sun, Jing; Yan, Chao-Guo (Beilstein Journal of Organic Chemistry, 2018)
The pillar[5]arene mono- and di(oxyalkoxy)benzoic acids were successfully prepared in high yields by sequential alkylation of ω-bromoalkoxy-substituted pillar[5]arenes with methyl or ethyl p-hydroxybenzoate followed by a hydrolytic reaction under basic conditions. Under catalysis of HOBt/EDCl, the amidation reaction of pillar[5]arene mono(oxybutoxy)benzoic acid with monoamido-functionalized pillar[5]arenes afforded diamido-bridged bis-pillar[5]arenes. 1H NMR and 2D NOESY spectra clearly indicated that [1]rotaxanes were formed by insertion of longer diaminoalkylene unit into the cavity of one pillar[5]arene with another pillar[5]arene acting as a stopper. The similar catalysed amidation reaction of pillar[5]arene di(oxybutoxy)benzoic acid with monoamido-functionalized pillar[5]arenes resulted in the diamido-bridged tris-pillar[5]arenes, which successfully form the unique bis-[1]rotaxanes bearing longer than diaminopropylene diamido bridges.
Keywords: bis-[1]rotaxane; mechanically interlocked molecule; pillar[5]arene; [1]rotaxane; self-assembly